Remembering to Prevent: The Preventive Capacity of Public Memory - Kerry E. Whigham (Genocide Studies and Prevention: An International Journal, 2017)
It is without doubt the case that memory of the past has been and is being used in certain places to justify radical intolerance and unspeakable violence. But for every instance where that is the case, a dozen alternative cases exist where memory creates cohesion, positive change, and a less violent society. This article focuses on the instances where memory does the latter. It first discusses why and how the formation of a public memory culture can be preventive of future violence. Next, it introduces several categories of memory practices, each of which exemplifies the embodied nature of public memory, and each of which demonstrates the capacity for memory to bring people together, rather than tear them apart. This survey of memory practices illustrates an array of successful means for both remembering the past and preventing violence in the future.